2009
DOI: 10.1021/ac900573x
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Picoliter-Scale Translational Spontaneous Sample Introduction for High-Speed Capillary Electrophoresis

Abstract: A novel microfluidic picoliter-scale sample introduction approach was developed by combining the spontaneous injection approach with a capillary electrophoresis (CE) system based on a short capillary and slotted-vial array. A droplet splitting phenomenon at the capillary inlet end during the spontaneous sample introduction process was observed for the first time. On the basis of this phenomenon, a translational spontaneous injection approach was established to reduce sample injection volumes to the sub-100 pL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 30 publications
1
81
0
Order By: Relevance
“…1, which is similar to that reported previously [17], except that 0.2-mL slotted plastic centrifuge tubes were used for containing sample and buffer solutions instead of the slotted sandwich reservoirs. Briefly, the capillary was fixed on a glass plate with a hole (ca.…”
Section: Hsce Systemmentioning
confidence: 55%
See 2 more Smart Citations
“…1, which is similar to that reported previously [17], except that 0.2-mL slotted plastic centrifuge tubes were used for containing sample and buffer solutions instead of the slotted sandwich reservoirs. Briefly, the capillary was fixed on a glass plate with a hole (ca.…”
Section: Hsce Systemmentioning
confidence: 55%
“…However, for a HSCE system based on a short capillary with an effective separation length of a few centimeters, narrow sample plugs o100 mm are usually essential to ensure sufficient separation efficiency. The translational spontaneous injection technique offers a promising way to obtain narrow sample plugs required in HSCE systems [17].…”
Section: Partial Spontaneous Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that short capillary-based CE systems can achieve high-speed and high-efficiency separation [32,33]. In this study, a 14 cm long Teflon AF-coated fused silica capillary served as the separation channel to ensure rapid DNA separation.…”
Section: Design Of the Stgce Systemmentioning
confidence: 98%
“…22 Subsequently, they made extensive improvements on a slotted-vial array sample introduction device, and achieved the goal of sampling automation on a microfluidic platform. [23][24][25][26] All of the studies described above, mainly focused on sample introduction. Yet, there have been distinct requirements to fulfill multiple functions, including chip cleaning and activation, since these procedures are prerequisites for chip electrophoresis.…”
Section: Introductionmentioning
confidence: 99%